Music for pain relief during bed bathing of mechanically ventilated patients: A pilot study. - Gwenaëlle Jacq; Karine Melot; Mathilde Bezou; Laura Foucault; Josette Courau-Courtois; Sebastien Cavelot; Annie Lang; Jean-Pierre Bedos; Dominique Le-Boeuf; Jean-Marc Boussard; Stephane Legriel (PLoS ONE, 2018)
BACKGROUND:Pain is a universal issue and is of particular concern in mechanically ventilated patients, as they require intensive nursing care and multiple invasive procedures, while being unable to communicate verbally. The aim of this study was to assess the effect of music on pain experienced by mechanically ventilated patients during morning bed bathing. METHODS:Of the 60 mechanically ventilated patients enrolled in this single-center pilot study between March 2013 and October 2015, the first 30 received no music and the next 30 the music intervention, during the morning bed bath. The Behavioral Pain Scale (BPS) score was determined during and at the end of the bath then 30, 60, and 120 minutes after the bath. BPS score changes over time were assessed and the proportions of bath times spent with a BPS score ≥5 and with the maximal BPS score were determined. RESULTS:At baseline, no patient had pain (defined as a BPS score <5) and the median BPS score was 3 [IQR, 3;3] in both groups (P = 0.43). After bed bath initiation, 88% of patients experienced pain. The maximum BPS value during the bath was lower in the music group (5 [5;6.7] vs. 7 [5;7]). Proportions of total bath time spent with BPS≥5 and with the maximum BPS were significantly lower in the music group than in the control group (2.0 [0.3;4.0] vs. 10 [4.3;18.0]; P < .0001 and 1.5 [0;3.0] vs. 3.5 [2.0;6.0]; P = .005; respectively). Two hours after the end of the bath, the BPS values had returned to baseline in both groups. CONCLUSION:In our population, music significantly decreased pain intensity and duration during the morning bed bath in mechanically ventilated patients. These results warrant further assessment in a large multicenter randomized controlled trial. TRIAL REGISTRATION:ClinicalTrials.gov NCT02883959.